2012
DOI: 10.1371/journal.pone.0052965
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression of Margatoxin and Agitoxin-2 in Pichia pastoris: An Efficient Method for Production of KV1.3 Channel Blockers

Abstract: The Kv1.3 voltage-gated potassium channel regulates membrane potential and calcium signaling in human effector memory T cells that are key mediators of autoimmune diseases such as multiple sclerosis, type 1 diabetes, and rheumatoid arthritis. Thus, subtype-specific Kv1.3 blockers have potential for treatment of autoimmune diseases. Several Kv1.3 channel blockers have been characterized from scorpion venom, all of which have an α/β scaffold stabilized by 3–4 intramolecular disulfide bridges. Chemical synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
(62 reference statements)
4
16
1
Order By: Relevance
“…When MgTx was isolated and its high affinity interaction with Kv1.3 was precisely characterized it was only tested on a limited number of channels excluding Kv1.1, Kv1.2 and Kv1.4 channels, those with high sequence homology to Kv1.3 (Garcia-Calvo et al, 1993). Later the authors who described MgTx and other workgroups refer to the peptide as potent blocker of Kv1.1, Kv1.2 and Kv1.3 channels (Anangi et al, 2012;Koch et al, 1997;SuarezKurtz et al, 1999;Vianna-Jorge et al, 2003) whereas the references do not describe or contain any information about the interaction of MgTx and the Kv1.1 or Kv1.2 channels. Without the precise characterization of the selectivity profile of MgTx, results from radioactively labeled MgTx binding assays, observed potassium current block or other biological effects of the peptide may not be considered as a direct proof of Kv1.3 expression.…”
Section: Toxicon XXX (2014) 1e11mentioning
confidence: 99%
“…When MgTx was isolated and its high affinity interaction with Kv1.3 was precisely characterized it was only tested on a limited number of channels excluding Kv1.1, Kv1.2 and Kv1.4 channels, those with high sequence homology to Kv1.3 (Garcia-Calvo et al, 1993). Later the authors who described MgTx and other workgroups refer to the peptide as potent blocker of Kv1.1, Kv1.2 and Kv1.3 channels (Anangi et al, 2012;Koch et al, 1997;SuarezKurtz et al, 1999;Vianna-Jorge et al, 2003) whereas the references do not describe or contain any information about the interaction of MgTx and the Kv1.1 or Kv1.2 channels. Without the precise characterization of the selectivity profile of MgTx, results from radioactively labeled MgTx binding assays, observed potassium current block or other biological effects of the peptide may not be considered as a direct proof of Kv1.3 expression.…”
Section: Toxicon XXX (2014) 1e11mentioning
confidence: 99%
“…When Lys28 is mutated to Ala, MgTx's ability to inhibit Kv1.3 is abolished (Anangi et al . ). Although we had no direct control over which basic residues were targeted during the conjugation to QDs, our electrophysiological data demonstrated that chemical conjugation through this methodology did not prevent MgTx from inhibiting Kv1.3, thus it is highly likely that our conjugation did not significantly affect the surface residues required to form favorable electrostatic interactions with the channel.…”
Section: Discussionmentioning
confidence: 97%
“…Of all the scorpion venom peptides that have been isolated, margatoxin (MgTx) and hongotoxin (HgTx) are among the most potent for Kv1.3. Both toxins inhibit Kv1.3 with picomolar affinities [ 8 , 9 ], but they are equally potent for several other Kv channel isoforms such as Kv1.1 and Kv1.2, which are closely related to Kv1.3 [ 8 , 10 ]. For the pharmacological development of MgTx and HgTx the specificity of the toxins for Kv1.3 needs to be improved.…”
Section: Introductionmentioning
confidence: 99%